The Reaction of Myocardial Capillaries to Crystalloid Cardioplegia of Different Durations in Patients with Valvular Pathology and Coronary Heart Disease - Zakharova, Valentina P.; Krykunov, Oleksii A.; Semeniv, Petro M.; Balabai, Alina A.; Hulich, Andrii A. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To study the morphological manifestations of the response of the myocardial capillaries to cardioplegia in patients with valvular defects and coronary heart disease. Materials and methods. Morphological research of operative and sectional material was carried out. Myocardium fragments for microscopical study were obtained from patients at different stages of an open-heart surgery and patients who died at the stage of conservative treatment without surgical intervention. Similar samples of the myocardium of a healthy young man who died from injuries incompatible with life were studied as a control. For electron microscopy study, samples of myocardium were taken from patients at the 185th minute of perfusion. Results. Histological preparations of the myocardium showed pronounced diffuse hypertrophy of cardiomyocytes (CMCs), sometimes at the stage of decompensation (perinuclear edema, loss of myofibrils, apoptosis). This transformation of CMCs was obviously related to their functional overload caused by combined defects of the mitral and aortic valves. Changes in muscle fibers were accompanied by interstitial and perinuclear fibrosis. In the pool of coronary arteries affected by atherosclerosis, signs of small focal coronary fibrosis were visible, as well as rough post-infarction scars in 3 patients. All the patients had signs of acute hypoxic damage to the myocardium in the form of CMCs shortening and interstitial edema. Conclusions. In patients with combined defects of the aortic and mitral valves of the heart with coronary artery disease, the phenomena of myocardial fibrosis prevail. Heart valve disease combined with coronary heart disease lead to the development of both alterative and compensatory-adaptiveprocesses in the vessels of the microcirculatory bed. The greatest loss of vital organelles in small vessels is observed at 185 min after administration of cardioplegic solution, irreversible changes develop 3 h after perfusion.